Three-Stage Membrane Treatment of Wastewater from Biodiesel Production-Preliminary Research - Magdalena Lech; Agnieszka Klimek; Damian Porzybót; Anna Trusek (Membranes, 2021)
As biodiesel production as renewable fuel increases, so does the amount of wastewater resulting from this technology. Wastewater is generated during the so-called biodiesel washing, i.e., washing out glycerol and methanol with water. The purified biodiesel must meet international standards, such as EN 14214 or the American ASTM D6751 standard. To fully say that biodiesel technology is environmentally friendly, the amount of wastewater should be minimized. It is also desirable that the purified water can be recycled to the technology. For this purpose, wastewater pre-treated by flotation, during which mainly oils are removed, was subjected to three-stage membrane separation. For each of the stages, the membrane was selected and characterized in terms of its separation capacity and stream stability. Starting with microfiltration, which was mainly aimed at reducing turbidity, affects the permeate flux in the following steps. Then, ultrafiltration and nanofiltration membranes were selected. These membranes were aimed at reducing the concentration of inorganic and organic substances. Consequently the cascade was composed of: MF-0.45 µm, UF-150 kDa, and NF-characterized by an 80% degree of desalination. The final permeate has a salt concentration of less than 0.15 g/L and can be reused in biodiesel technology.